A Mobile Gaming Intervention for Persons on Pre-Exposure Prophylaxis: Protocol for Intervention Development and Randomized Controlled Trial - Whiteley, Laura; Olsen, Elizabeth; Mena, Leandro; Haubrick, Kayla; Craker, Lacey; Hershkowitz, Dylan; Brown, Larry K (JMIR research protocols, 2020)
In the United States, young minority men who have sex with men (MSM) are the most likely to become infected with HIV. Pre-exposure prophylaxis (PrEP) is an efficacious and promising prevention strategy. However, PrEP's safety and effectiveness can be greatly compromised by suboptimal adherence to treatment. To maximize the positive impact of PrEP, it is necessary to combine its prescription with cost-effective behavioral interventions that promote adherence and decrease HIV risk behaviors. In this project, we developed a theoretically informed app/gaming intervention to engage young MSM in learning information, practicing behaviors, and improving motivation for HIV preventative behaviors and PrEP adherence. The goal of this project was to develop and test a cutting-edge, engaging, and entertaining app/gaming intervention for improving adherence to PrEP and building HIV prevention knowledge, skills, and behavior. This study was conducted in two phases. In the developmental phase, we conducted qualitative interviews with young MSM (n=20) to guide the development of the gaming intervention. In the randomized controlled trial, we tested the preliminary efficacy of the gaming intervention compared to a comparison condition among young MSM. Subjects were recruited from the University of Mississippi Medical Center HIV/STI testing clinics (n=60). Institutional review board approval was received in February 2015. Research activities began in June 2015 and are still ongoing. This app/gaming intervention aimed to improve PrEP adherence and HIV preventative behaviors in young MSM. Engaging young MSM in learning information, practicing behaviors, and improving motivation for increased adherence to PrEP has the potential to decrease HIV seroconversion. It is important to develop interventions that are enjoyable, engaging, and easily incorporated into clinical settings. ClinicalTrials.gov RCT02611362; https://tinyurl.com/y65gkuwr. DERR1-10.2196/18640.